2014
DOI: 10.1186/s12866-014-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro combination therapy using low dose clotrimazole and photodynamic therapy leads to enhanced killing of the dermatophyte Trichophyton rubrum

Abstract: BackgroundSuperficial infections of the skin and mucous membranes caused by dermatophyte fungi are amongst the most common and challenging infections to treat. Previously we demonstrated the phototoxic effects of photodynamic therapy (PDT) towards Trichophyton rubrum, using a green laser to photoactivate Rose Bengal (RB). The aim of this study was to evaluate whether we could; (1) achieve a similar effect using an inexpensive light-emitting diode (LED) to photoactivate RB and (2) to evaluate whether our PDT re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…12,13 The efficacy of rose bengal, a commonly used ocular stain, as an alternate photosensitizer has been investigated for inhibiting the growth of microbial isolates. [14][15][16] One group found the minimum concentration of rose bengal needed to inhibit fungal isolates to be 280 µM (0.03%), which was used as one of the concentrations of rose bengal in our study. 16 It was hypothesized that PDT is effective in eradicating multidrugresistant MRSA strains in vitro.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…12,13 The efficacy of rose bengal, a commonly used ocular stain, as an alternate photosensitizer has been investigated for inhibiting the growth of microbial isolates. [14][15][16] One group found the minimum concentration of rose bengal needed to inhibit fungal isolates to be 280 µM (0.03%), which was used as one of the concentrations of rose bengal in our study. 16 It was hypothesized that PDT is effective in eradicating multidrugresistant MRSA strains in vitro.…”
Section: Introductionmentioning
confidence: 91%
“…[14][15][16] One group found the minimum concentration of rose bengal needed to inhibit fungal isolates to be 280 µM (0.03%), which was used as one of the concentrations of rose bengal in our study. 16 It was hypothesized that PDT is effective in eradicating multidrugresistant MRSA strains in vitro. To test this, two clinical MRSA strains were exposed to 0.03% and 0.1% rose bengal-mediated PDT and 0.1% riboflavin-mediated PDT and observed for growth inhibition.…”
Section: Introductionmentioning
confidence: 91%
“…The effectiveness of photo-activated RB against Fusarium keratoplasticum fungi in keratitis both in vitro and in vivo was also demonstrated by dropping RB solution into the patient's eye and irradiating it in the operating room, 41 and against Trichophyton rubrum. 2,42 As discussed by Spagnul et al, 3 RB for antimicrobial PDT can be incorporated into natural polymers, such as in chitosan nanoparticles or on to cellulose acetate surfaces. Manoil et al 43 discussed the use of RB-Acetate against Enterococcus faecalis, resulting in reduced bacterial viability, whereas Decraene et al 44 demonstrated reduced environmental contamination on clinical surfaces by using cellulose RB-Acetate coatings.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…In vitro methods using PDT have been widely performed against several species of microorganisms, including bacteria, viruses, protozoa, and fungi (Arboleda et al, 2014;Brooks et al, 1994;Choi et al, 2014;Lim et al, 2012;Lyon et al, 2011;Makarov et al, 2014;Morton et al, 2014;Rossoni et al, 2014;Sabino et al, 2015;Soares et al, 2011;Song et al, 2011;Takahashi et al, 2014). Silva et al (2015) report that after cancer, infections represent the next most frequent application of PDT.…”
Section: Photodynamic Therapy (Pdt) Using Natural Compoundsmentioning
confidence: 99%